2015
DOI: 10.1149/2.0021604jes
|View full text |Cite
|
Sign up to set email alerts
|

Scanning Electrochemical Microscopy and Hydrodynamic Voltammetry Investigation of Charge Transfer Mechanisms on Redox Active Polymers

Abstract: We recently showed that viologen-based redox active polymers (RAPs) with molecular weights between 21 and 318 kDa are attractive charge storage materials as anolytes for size-selective non-aqueous redox flow batteries. Here, we characterize the electron transfer mechanisms of these RAPs, as well as a ferrocene based catholyte RAP, in acetonitrile/Li + electrolyte. We utilized scanning electrochemical microscopy (SECM) and rotating disk electrode (RDE) voltammetry to measure the rate of electron transfer and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
48
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(56 citation statements)
references
References 49 publications
4
48
0
Order By: Relevance
“…Considering the peak currents at 0.1 and 1 V s −1 (4.6 and 39.9 μA), as well as the quotient between 1 and 2, D e was estimated to be about 4.86×10 −11 cm 2 s −1 . This value is in the order of magnitude for different ferrocene polymers for which this parameter has been reported to be between 10 −9 to 10 −12 cm 2 s −1 , depending on the film thickness and structure [54–56] . More interconnected structures like metal‐organic frameworks have values in a wider range (10 −7 to 10 −12 cm 2 s −1 ) [57,58] …”
Section: Resultsmentioning
confidence: 86%
“…Considering the peak currents at 0.1 and 1 V s −1 (4.6 and 39.9 μA), as well as the quotient between 1 and 2, D e was estimated to be about 4.86×10 −11 cm 2 s −1 . This value is in the order of magnitude for different ferrocene polymers for which this parameter has been reported to be between 10 −9 to 10 −12 cm 2 s −1 , depending on the film thickness and structure [54–56] . More interconnected structures like metal‐organic frameworks have values in a wider range (10 −7 to 10 −12 cm 2 s −1 ) [57,58] …”
Section: Resultsmentioning
confidence: 86%
“…There have been not enough systematic studies, however, on the influence of the polymer solubility on battery performance. 107 Most recently in 2017, Jia et al reported the effect of molecular weight on the electrochemical properties of a redox-active polymer, poly(TEMPO methacrylate) (PTMA). 108 In this study, single electron transfer-living radical polymerization (SET-LRP) was utilized to synthesize poly(2,2,6,6-tetramethylpiperidine methacrylate) (PTMPM) with controllable molecular weight and low dispersity (Figure 6A).…”
Section: Molecular Weight Control Of Redox-active Polymermentioning
confidence: 99%
“…[12,17,18] Charge hopping on redox-active polymers has been investigated in solution, [19][20][21] as films on modified electrodes, [21,22] and with isolated molecules. Electron transfer at the electrode-particle interface and subsequent charge hopping enables particle electrolysis via the movement of charge between the oxidized (V 2 + ), and the reduced state (V + ).…”
Section: Introductionmentioning
confidence: 99%